2016
DOI: 10.5539/jms.v6n3p79
|View full text |Cite
|
Sign up to set email alerts
|

Humanitarian Demining and Sustainable Land Management in Post-Conflict Settings in Sri Lanka: Literature Review

Abstract: Systematic humanitarian demining carried out with care is an essential prerequisite for sustainable land management in post conflict settings. Degradation of land and pollution of water, soil and vegetation, as well as poisonous gas emissions that may even contribute to climate change, can be reduced significantly by humanitarian demining practices. Such practices simultaneously conserve natural resources and increase yields which results to sustainable land management. Mine Risk Education which is a major com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Tab.-8 Short-term returns are significantly higher than the maintenance cost of SLM (Jendoubi et al, 2015) also showed the same findings. Moreover, farmers also knew that diversity of sources also increased because of SLM and that was beneficial for them both in the short run and long run (Gunawardana, Tantrigoda, & Kumara, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tab.-8 Short-term returns are significantly higher than the maintenance cost of SLM (Jendoubi et al, 2015) also showed the same findings. Moreover, farmers also knew that diversity of sources also increased because of SLM and that was beneficial for them both in the short run and long run (Gunawardana, Tantrigoda, & Kumara, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the return is expected to be yielded after a longer period of time so farmers cannot wait that long to fulfill their needs. In addition, farmers may not have enough capital for SLM so they need external loans from lending institutions, which means that cost of borrowing is also incurred (Halbac-Cotoara-Zamfir, Herban, Petursdottir, & Finger, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Also, the return is expected to be yielded after a longer period of time so farmers cannot wait that long to fulfill their needs. In addition, farmers may not have enough capital for SLM so they need external loans from lending institutions, which means that cost of borrowing is also incurred (Halbac-Cotoara-Zamfir, Herban, Petursdottir, & Finger, 2017).…”
Section: Background Of the Studymentioning
confidence: 99%
“…Accordingly, it has been proven that the clearing of mine contaminated areas with a high priority [7] has a significant impact on the standard of living ( [3], [5], [6]). Furthermore, priority setting increases sustainability of humanitarian demining, emphasizing not only economical aspect but also social and ecological aspects ( [9], [10]). During the last 20 years, MCA/MCDM methods have been used intensively in the management of mine action projects: from complete decision support systems ( [1], [15], [20], [22], [23]) to the application of various MCDM methods ( [4], [27]).…”
Section: State-of-the-artmentioning
confidence: 99%